Predicting invasiveness of freshwater fishes imported into North America: regional differences in models and outcomes - Jennifer G. Howeth; Sarah A. Amjad; Crysta A. Gantz; Nicholas E. Mandrak; Paul L. Angermeier; Michael P. Marchetti; Julian D. Olden; David M. Lodge (Biological Invasions, 2025)
Biological invasions driven by international trade heighten the urgency for development of invasion risk models, as the traits and parameters that consistently predict successful invasion remain unresolved. For four regions of North America that include parts of the United States and Canada (Sacramento-San Joaquin River Basins, Lower Colorado River Basin, Great Lakes Region, Mid-Atlantic Region), we construct and compare classification tree models to reveal robust predictors for the establishment and ecological impact stages of freshwater fish invasion. We subsequently apply the models to identify invasive fish species in trade and conduct pathway analyses to determine which trades (aquarium, biological supply, live bait, live food, water garden) and source continents pose the greatest risk to each region. Model results differed by invasion stage and region. Across regions, establishment models shared climate-related predictors including climate match and temperature tolerance. Three of the four impact models contained prior establishment success. The greatest number of species (548) were predicted to establish in the Sacramento-San Joaquin while the fewest (5) were predicted to establish in the Mid-Atlantic. Forty species were predicted to establish in multiple regions, five of which were also predicted to have high impact. The aquarium trade and Asia supplied the most species predicted to establish. Taken together, the results highlight region-specific models, indicating no universal model predicts invasion. Climate-related and prior establishment variables were most useful to risk assessments. The regional models, and identified high-risk pathways and potential invaders, could be applied to prevent future fish invasions in North America.

Zebra mussels (Dreissena polymorpha) influence reservoir ecosystem attributes along southern invasion front metaecosystems in North America - Riley T. Lovejoy; Alyssa N. Kandow; Jennifer G. Howeth (Hydrobiologia, 2025)

Functional trait sorting increases over succession in metacommunity mosaics of fish assemblages - C. Thomas Olinger; Justin L. Hart; Jennifer G. Howeth (Oecologia, 2021)

Predation inhibits the positive effect of dispersal on intraspecific and interspecific synchrony in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2013)
Recent interest in the ecological drivers of compensatory and synchronous population dynamics has provided an improved yet incomplete understanding of local and regional population oscillations in response to variable environments. Here, we evaluate the effect of dispersal rate and spatiotemporal heterogeneity in predation by the selective planktivore, bluegill sunfish ( Lepomis macrochirus ), on local and regional dynamics of zooplankton in pond metacommunities. A metacommunity consisted of three pond mesocosm communities, one with constant presence of predators, one without predators, and one with alternating presence–absence of predators. The three communities were connected at either no, low (0.7% per day), or high (20% per day) planktonic dispersal. Results demonstrate that heterogeneous predation (1) prevents spatial synchrony among prey populations across local communities, (2) disrupts the synchronous population dynamics within communities produced by dispersal, and (3) induces local compensatory dynamics between species within communities regardless of dispersal rate. Taken together, the results emphasize that spatiotemporal heterogeneity in selective predation can inhibit both intraspecific and interspecific synchrony in metacommunities.

Species dispersal rates alter diversity and ecosystem stability in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology, 2010)
Metacommunity theory suggests that relationships between diversity and ecosystem stability can be determined by the rate of species dispersal among local communities. The predicted relationships, however, may depend upon the relative strength of local environmental processes and disturbance. Here we evaluate the role of dispersal frequency and local predation perturbations in affecting patterns of diversity and stability in pond plankton metacommunities. Pond metacommunities were composed of three mesocosm communities: one of the three communities maintained constant “press” predation from a selective predator, bluegill sunfish ( Lepomis macrochirus ); the second community maintained “press” conditions without predation; and the third community experienced recurrent “pulsed” predation from bluegill sunfish. The triads of pond communities were connected at either no, low (0.7%/d), or high (20%/d) planktonic dispersal. Richness and composition of zooplankton and stability of plankton biomass and ecosystem productivity were measured at local and regional spatial scales. Dispersal significantly affected diversity such that local and regional biotas at the low dispersal rate maintained the greatest number of species. The unimodal local dispersal–diversity relationship was predator‐dependent, however, as selective press predation excluded species regardless of dispersal. Further, there was no effect of dispersal on beta diversity because predation generated local conditions that selected for distinct community assemblages. Spatial and temporal ecosystem stability responded to dispersal frequency but not predation. Low dispersal destabilized the spatial stability of producer biomass but stabilized temporal ecosystem productivity. The results indicate that selective predation can prevent species augmentation from mass effects but has no apparent influence on stability. Dispersal rates, in contrast, can have significant effects on both species diversity and ecosystem stability at multiple spatial scales in metacommunities.

Contrasting demographic and genetic estimates of dispersal in the endangered Coahuilan box turtle: a contemporary approach to conservation - JENNIFER G. HOWETH; SUZANNE E. MCGAUGH; DEAN A. HENDRICKSON (Molecular Ecology, 2008)
The evolutionary viability of an endangered species depends upon gene flow among subpopulations and the degree of habitat patch connectivity. Contrasting population connectivity over ecological and evolutionary timescales may provide novel insight into what maintains genetic diversity within threatened species. We employed this integrative approach to evaluating dispersal in the critically endangered Coahuilan box turtle ( Terrapene coahuila ) that inhabits isolated wetlands in the desert‐spring ecosystem of Cuatro Ciénegas, Mexico. Recent wetland habitat loss has altered the spatial distribution and connectivity of habitat patches; and we therefore predicted that T. coahuila would exhibit limited movement relative to estimates of historic gene flow. To evaluate contemporary dispersal patterns, we employed mark–recapture techniques at both local (wetland complex) and regional (intercomplex) spatial scales. Gene flow estimates were obtained by surveying genetic variation at nine microsatellite loci in seven subpopulations located across the species’ geographical range. The mark–recapture results at the local spatial scale reveal frequent movement among wetlands that was unaffected by interwetland distance. At the regional spatial scale, dispersal events were relatively less frequent between wetland complexes. The complementary analysis of population genetic substructure indicates strong historic gene flow (global F ST = 0.01). However, a relationship of genetic isolation by distance across the geographical range suggests that dispersal limitation exists at the regional scale. Our approach of contrasting direct and indirect estimates of dispersal at multiple spatial scales in T. coahuila conveys a sustainable evolutionary trajectory of the species pending preservation of threatened wetland habitats and a range‐wide network of corridors.

Planktonic dispersal dampens temporal trophic cascades in pond metacommunities - Jennifer G. Howeth; Mathew A. Leibold (Ecology Letters, 2008)
Trophic cascades, in which changes in predation affect the biomass of lower trophic levels, vary substantially in strength and incidence. Most work to explain this variation has focused on local factors and has ignored larger regional effects. To study how metacommunity dynamics can alter trophic cascades, we constructed mesocosm metacommunities consisting of three pond communities with heterogeneous levels of fish predation and examined how planktonic dispersal rate (5–140% per week) affected biomass partitioning. Two of the three communities differed continually in the occurrence of fish and supported different but constant environments in a ‘spatial trophic cascade,’ while the third community supported temporally variable fish occurrence in a ‘temporal trophic cascade.’ We find that the presence, but the not the magnitude, of dispersal dampens temporal trophic cascades through an increase in grazer biomass. In contrast, dispersal has no effect on the strength of spatial cascades due to strong sorting pressures in the communities with constant presence or absence of fish as top predators.